2023
DOI: 10.1007/s00170-023-11778-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cu donor material assisted friction stir welding of AA2024 and AA6061 dissimilar alloys: Effect on downward force, temperature profile, and mechanical properties

Abstract: In this research, the authors investigated copper (Cu) donor material assisted friction stir welding (FSW) of AA2024-T4 and AA6061-T6 aluminum plates of 6.35 mm thickness. FSW joints were prepared at optimized process parameters at a constant tool rotational rate of 1400 rpm and welding speeds at 1, 2, or 3 mm/s. The Cu donor material of 25% and 50% thickness with respect to the workpiece thickness were selected to assist the FSW joining at the plunge stage. During the welding processes, it was observed that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Therefore, this technology is frequently used to join metals or polymers [ 7 ]. Bhukya et al [ 8 ] investigated its effect on the mechanical properties, downward force, and temperature profile of an aluminum alloy using friction stir welding. The results revealed that low force was decreased after introducing the copper donor.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this technology is frequently used to join metals or polymers [ 7 ]. Bhukya et al [ 8 ] investigated its effect on the mechanical properties, downward force, and temperature profile of an aluminum alloy using friction stir welding. The results revealed that low force was decreased after introducing the copper donor.…”
Section: Introductionmentioning
confidence: 99%